2020
DOI: 10.3390/app10062041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight of Tilapia (Oreochromis Niloticus) Skin Collagen Peptide Fractions on Zinc-Chelating Capacity and Bioaccessibility of the Zinc-Peptide Fractions Complexes in Vitro Digestion

Abstract: To investigate the effect of the molecular weight of tilapia skin collagen peptide fractions on their zinc chelation capacity and the bioaccessibility of their zinc complexes, we evaluated the zinc-chelating ability of different molecular weight peptide, the solubility, and the stability of the complexes during simulated in vitro digestion. Low molecular weight peptide (P1) exhibited a higher zinc-chelating ability, which can be attributed to the variety of metal chelate amino acid residues. The highest solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Chen at al. found that compared with other two peptides with different average molecular weights (P2: 2,745 Da, P3: 4,378 Da), peptide with low molecular weight (P1:1,653 Da) had stronger zinc chelation capacity and stability ( 24 ). In addition, chicken muscle peptides (>10 kDa) showed excellent chelation capacity with iron ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chen at al. found that compared with other two peptides with different average molecular weights (P2: 2,745 Da, P3: 4,378 Da), peptide with low molecular weight (P1:1,653 Da) had stronger zinc chelation capacity and stability ( 24 ). In addition, chicken muscle peptides (>10 kDa) showed excellent chelation capacity with iron ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…This shift may be due to the electron‐withdrawing effect of Zn 2+ and the nitrogen atoms can form coordination bonds with zinc ions by offering their electron pairs; the hydrogen bonds were replaced with Zn‐N bonds (Sun et al ., 2021). Compared to the three peptides, their corresponding peptide‐zinc complexes in the amide I band (1700–1600 cm −1 ) and amide II (1600–1500 cm −1 ) are shifted, which was attributed to the C=O stretching vibrations coupled with the bending vibrations of N‐H, as well as N‐H bending coupled with C‐N stretching (Chen et al ., 2020). The peaks of ‐COO‐ at 1400 cm −1 were all significantly shifted in the peptide‐zinc complexes, which probably resulted from the replacement of H with zinc.…”
Section: Resultsmentioning
confidence: 99%
“…The MW distribution of THPH were measured following the method of Chen et al [ 31 ]. Briefly, a Waters (Waters Corporation, Milford, MA, USA) 1525 HPLC system with a silica-based column (TSK-GEL G2000 SWXL, Shimadzu, Tokyo, Japan) was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%